Floodresc – Disaster Management in case of Flooding in the Hernad Watershed - Dobos, Endre; Vágó, János; Pecsmány, Péter; Blistan, Peter; Zelenáková , Martina; Ladányi, Richárd; Kiss, Levente (International Journal of Engineering and Management Sciences, 2019)
The aim of the Floodresc project is to develop a GIS based decision support system that can help the defense and rescue operations of the Disaster Management Directorate during any floods in the Hernád River. In the project, a geospatial database covering the entire river basin, a modeling application for predicting the extent of flooded areas in time, and a logistics model supporting defense-related transportation tasks will be developed.